Health issues and green space as reinforcement for a healthy lifestyle in Malaysia - Mansor, Mazlina; Harun, Nor Zalina (Association of MaMalaysian Environment-Behaviour Researchers (AMER); ABRAmalaysia, 2018)
A rise in non-communicable diseases (NCDs) is predominantly due to unhealthy urban lifestyle such as work stress, being sedentary and unhealthy eating habits. This paper identifies health issues in Malaysia, and it reviews preventive measures to make people aware of the importance of healthy living. The paper contends that green space is beneficial, which encourage people to make good choices about their health. It reviews researches that show that green space supports greater outdoor activities and influence healthy behaviors of city residents. Thus, green space is a significant health promotion agenda that improves the urban quality of life.